A longitudinal analysis on the validity and reliability of ratings of perceived exertion for elite swimmers - Psycharakis, S. G. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to examine longitudinally the reliability and validity of ratings of perceived exertion (RPE) for monitoring exercise intensity in elite swimmers, with the percentage of maximum heart rate (%HRmax) and the blood lactate concentration (La) being the criterion measures. Moreover, the purpose was to examine whether an adjustment of HRmax, as previously suggested for recreational/university swimmers, is required for subsequent calculations of %HRmax for elite swimmers. Seventeen swimmers competing at international level performed a 7 x 200 m incremental swim test at their specialty stroke 4 times during a period of 6 months. The RPE validity was examined with the use of correlation and with repeated measures analysis of variance (ANOVA) of the z-transformed values. The RPE reliability was examined with a factorial ANOVA, with %HRmax and La being the dependent variables and test (4 levels) and RPE stage (7 levels) the fixed factors. The RPE was found to be a valid method for monitoring exercise intensity, with the correlation coefficients with %HRmax and La being 0.85 and 0.82, respectively. There was a strong correspondence between RPE and %HRmax scores and a weaker correspondence between RPE and La scores, suggesting that that RPE reflects accurately the HR levels of elite swimmers. The longitudinal intertest reliability was high as no significant differences were found in the values of %HRmax or La between the 4 tests. The good validity and reliability of RPE suggest that it can be used in elite swimmers' training for the purpose of monitoring exercise intensity. Contrary to previous recommendations for recreational/university swimmers, when prescribing intensity for elite swimmers, the predicted HRmax value used for subsequent calculations should not be adjusted because such an adjustment would appear to underestimate HRmax.